Immunological determinants of tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) in HIV-infected patients on antiretroviral therapy / Tan Hong Yien - Tan, Hong Yien (2016)
The advent of combined antiretroviral therapy (cART) has improved the quality of life of human immunodeficiency virus (HIV)-infected individuals by suppressing viral replication leading to reconstitution of the immune system. However, patients initiated on cART at an immunodeficient state i.e. CD4+ T-cell counts <200 cells/μL, may experience immune reconstitution inflammatory syndrome (IRIS) characterized by exaggerated inflammatory responses against an existing opportunistic infection (OI). Tuberculosis (TB) represents the most common OI among individuals with HIV infection, especially in resource-limited settings. TB-associated IRIS (TB-IRIS) often manifests as paradoxical deterioration of treated TB (also known as paradoxical TBIRIS), or rapid onset of newly diagnosed TB following cART initiation (also known as unmasking TB-IRIS). Notwithstanding that 10–30% of TB-HIV co-infected patients may develop TB-IRIS, there has not been a report from Malaysia, heretofore. Hence, a retrospective investigation was conducted. The prevalence of TB-IRIS was 16% among TB-HIV coinfected patients at the University Malaya Medical Centre (UMMC). Only disseminated TB was predictive of TB-IRIS (OR=10.7, P=0.032), and that the mortality rates were similar between patients with TB-IRIS (n=1, 5.9%) and TB-HIV without IRIS (n=5, 5.7%). CD4+ T-cell recovery following ART was not different between the two groups. TB-IRIS reportedly occurs within the first month of ART, and hence it is cumbersome to distinguish it from relapsed or newly acquired TB. Therefore, there is an urgent need to identify appropriate laboratory markers to predict and characterize TB-IRIS. In a prospective cohort at UMMC, a case-control study that comprised the following study groups was established: (1) TB-IRIS (case) (2) TB no IRIS (control) (3) No TB or IRIS (control) The levels of twelve cytokines/pro-inflammatory mediators at baseline and at the event of TB-IRIS (or equivalent time-point for control) were compared among the three groups. We found that the plasma IL-18 was higher in TB-IRIS patients at pre-cART and during the event. CXCL10 was higher pre-cART (P<0.001), mainly in paradoxical TB-IRIS patients, and during TB-IRIS (P<0.001), whereas CXCL8 was only higher during TB-IRIS (P<0.001). In contrast, IFN-γ was lower before and during TB-IRIS. Receiver operating curve (ROC) analysis showed that CXCL10 (AUC=0.884, P<0.0001) and IL-18 (AUC=0.99, P<0.0001) at pre-cART were predictive of TB-IRIS. Since IL-18 is the signature cytokine for inflammasome activation in monocyte/macrophage, next we investigated the role of inflammasome activation and pyroptosis in the pathogenesis of TB-IRIS. HIV-TB patients exhibited higher proportions of monocytes expressing activated caspase 1 (casp1) pre-cART, compared to HIV patients without TB; patients who developed TB-IRIS exhibited increased casp1 levels following initiation of cART. TB-IRIS patients also had increased NLRP3 and AIM2 inflammasome mRNA, compared to controls. Expression of cell death markers (7-AAD and Annexin V by PBMC and plasma mitochondrial DNA (mtDNA) levels) was also higher in TB-IRIS patients. Plasma nitric oxide (NO) levels were lower precART in TB-IRIS patients suggest inadequate inflammasome regulation. Expression of IL-18Rα on CD4+ T cells and NK cells was higher in TB-IRIS patients post cART, providing evidence that receptiveness against IL-18 further increase inflammasome activation and pyroptosis in monocytes.